A new measure of international product innovation - Valeska V. Geldres-Weiss; Joaquín Monreal-Pérez; Dirceu Tornavoi-Carvalho; Jorge Tello-Gamarra (Contemporary Economics, 2018)
It is important for firms to undertake product innovation since this will enable them to incorporate additional value to its market offer and, consequently, will increase their international competitiveness. Thus, the aim of this article is to develop a new index, the Export Product Innovation Index (EPII), a metric that associates product innovation to export activity according to the value of new export products / goods traded abroad at a single company level. The proposed index is built on official export data and based on the Harmonized System Codes. Therefore, the EPII may be widely generalized and calculated for every export firm all over the world for which export shipping data is available, enabling benchmarks for companies, international comparative studies and policy making. This article uses data on Chilean fruit exporters to illustrate EPII calculation and use. Through the comparison of this new index with some previous ones measuring product innovation overall population of Chilean fruit exporters, it is demonstrated that the EPII provides more accurate information to appraise a firm's export product innovation performance.
Keywords: M16; F13; 330; Product Innovation; International Competitiveness; Export Product Innovation Index; Harmonized System Codes; Fruit Exports; Chile